Improvement of parameters of micro-pixel avalanche photodiodes. (1st July 2022) - Sadigov, A.Z.; Ahmadov, F.I.; Sadygov, Z.Y.; Ahmadov, G.S.; Berikov, D.; Holik, M.; Mammadli, A.; Akbarov, R.A.; Nuruyev, S.M.; Ajdarli, K.; Garibli, A.; Doganci, E.; et al.
Abstract: The paper is concerned with the parameter study of a new generation of micro-pixel avalanche photodiodes (MAPD) with deeply buried pixel structure, also named silicon photomultipliers (SiPM) or multi-pixel photon counter (MPPC). The new MAPD of type MAPD-3NM was manufactured in the frame of collaboration with Zecotek Company. Measurements were carried out and discussed in terms of the important parameters such as the current-voltage and capacitance-voltage characteristic, gain, the temperature coefficient of breakdown voltage, breakdown voltage, and gamma-ray detection performance using an LFS scintillator. The obtained results showed that the newly developed MAPD-3NM photodiode outperformed the previous generation in most parameters and can be successfully applied in space application, medicine, high-energy physics, and security. New proposals are also discussed, for further improvement of the parameters of the MAPD photodiodes that will be produced in the coming years.